The official Gold's Gym beginner's guide to fitness : the authority on fitness since 1965 - Porter, David, 1960-; Gold's Gym. (New York : McGraw-Hill, 2005)
With the help of instructive photographs shot on location at Gold's facilities, this book on fitness features tips on getting started and staying motivated, warming up and stretching, choosing the right exercises for your specific goals, avoiding injuries, and eating the right food.
Getting started -- Making time and staying motivated -- Types of training -- Safety and avoiding injury -- Exercise and pregnancy -- Stretching -- Weight training : the basics -- Specific training programs -- Supplemental exercises -- Alternative training -- Nutrition -- Buying home fitness equipment.
Includes index.
Keywords: Physical fitness; Exercise; Physical fitness; Sports training; Nutrition; Overseas item